Prevalence of anxiety, depressive and insomnia symptoms among the different groups of people during COVID-19 pandemic: An overview of systematic reviews and meta-analyses - Zou, Qi; Tang, Yuning; Jiang, Cheng; Lin, Pengyang; Tian, Jinhui; Sun, Shougang (Frontiers in Psychology, 2022)
We searched the Cochrane Library, PubMed and Web of Science to obtain systematic reviews and meta-analyses related to anxiety, depression, and insomnia in different populations during the COVID-19 pandemic. The methodological quality of the included literature was then evaluated using AMSTAR 2 tool. A subgroup analysis was performed of the prevalence of psychological disorders. A total of 42 SRs (8,200,330 participants) were included in calculating and assessing the prevalence of anxiety, depression, and insomnia in different populations (health care workers, college students, COVID-19 patients, and the general population). The results of the methodological quality evaluation showed that 13 SRs were rated "medium", 13 were rated "low", and 16 were rated "very low". The results of subgroup analysis showed that the prevalence of anxiety in different populations were: health care workers (20%-44%), college students (24%-41%), COVID-19 patients (15%-47%), general population (22%-38%); The prevalence of depression was 22%-38%, 22%-52%, 38%-45%, and 16%-35%, respectively; the prevalence of insomnia was 28%-45%, 27%-33%, 34%-48%, and 28%-35%, respectively. The comparison revealed a higher prevalence of psychological disorders in the COVID-19 patient group, with insomnia being the most pronounced. The methodological quality of SRs on the effects of anxiety, depression, and insomnia in different populations during the COVID-19 pandemic. Through the subgroup analysis, we found a higher prevalence of insomnia than anxiety and depression among the psychological disorders occurring in different populations during the pandemic, but the sample size on insomnia is small and more high-quality studies are needed to complement our findings.